2019
DOI: 10.1029/2018pa003417
|View full text |Cite
|
Sign up to set email alerts
|

Considerations for Globigerinoides ruber (White and Pink) Paleoceanography: Comprehensive Insights From a Long‐Running Sediment Trap

Abstract: We present a detailed analysis of the seasonal distribution, size, morphological variability, and geochemistry of co‐occurring pink and white chromotypes of Globigerinoides ruber from a high‐resolution (1–2 weeks) and long‐running sediment trap time series in the northern Gulf of Mexico. We find no difference in the seasonal flux of the two chromotypes. Although flux of G. ruber is consistently lowest in winter, the flux‐weighted signal exported to marine sediments represents mean annual conditions in the surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 107 publications
(217 reference statements)
1
27
0
Order By: Relevance
“…The predictions were run with δ18Ow of 1.66‰ and 0.86‰ (Vienna Standard Mean Ocean Water), based on the observed mean and range δ18Ow for the site. These predictions used HadISST monthly average SSTs (Rayner et al, ), which reasonably replicated buoy‐measured SST seasonality (Richey et al, ). All errors are ±1 standard deviation.…”
Section: Examples and Applicationsmentioning
confidence: 78%
See 3 more Smart Citations
“…The predictions were run with δ18Ow of 1.66‰ and 0.86‰ (Vienna Standard Mean Ocean Water), based on the observed mean and range δ18Ow for the site. These predictions used HadISST monthly average SSTs (Rayner et al, ), which reasonably replicated buoy‐measured SST seasonality (Richey et al, ). All errors are ±1 standard deviation.…”
Section: Examples and Applicationsmentioning
confidence: 78%
“…Solid green bars are the site modern annual or seasonal SST means ± 1 standard deviation, using monthly (1981–2017) NOAA Optimum Interpolation Sea Surface Temperature V2 (Reynolds et al, ). (b) The annual hierarchical calibration used to predict δ18Oc for G. ruber in the northern Gulf of Mexico, compared with averaged sediment trap observations (2010–2013) from Richey et al (). The predictions were run with δ18Ow of 1.66‰ and 0.86‰ (Vienna Standard Mean Ocean Water), based on the observed mean and range δ18Ow for the site.…”
Section: Examples and Applicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Richey et al () recently showed that there are two morphotypes of G. ruber (pink), corresponding to the sensu stricto and sensu latu morphotypes of G. ruber (white). While previous studies have shown that calcification can vary significantly between morphotypes (Marshall et al, ; Osborne et al, ), the Marshall et al () relationship, generated prior to the recognition of G. ruber (pink) morphotypes, proved robust without distinguishing between the two.…”
Section: Resultsmentioning
confidence: 99%